Management of various types of ectopic pregnancy - a questionnaire study - Švédová, Barbora; Hruda, Martin; Drochýtek, Vít; Halaška, Michael Jiří; Maxová, Kateřina; Janovská, Nikola; Součková, Helena; Babková, Anna; Rob, Lukáš; Sehnal, Borek (Ceska gynekologie, 2025)
OBJECTIVE: To map management of different types of ectopic pregnancies in the Czech Republic using a questionnaire-based study. METHODS: In 2023, a total of 95 obstetrics and gynecology departments across the Czech Republic were surveyed using an online questionnaire, which inquired about the management strategies for various types of ectopic pregnancies. The departments were categorized based on the number of hysterectomies performed annually. Differences in responses between large centers and other departments were statistically compared. RESULTS: A total of 45 departments of all sizes completed the questionnaire. Two-thirds of all departments always perform salpingectomy in cases of tubal pregnancy (78% of large, 58% of medium-sized, and 40% of small departments). Systemic methotrexate administration for the treatment of intact tubal pregnancy is used by one-fifth of departments (22% of large, 23% of medium-sized, and 0% of small departments). In cases of atypical ectopic pregnancy localization, methotrexate treatment is used by 33% of large, 42% of medium-sized, and 40% of small departments. A statistically significant difference was observed in the clearly preferred laparoscopic approach for surgical management of cesarean scar pregnancy in large centers compared to smaller departments (P = 0.036). No other statistically significant differences were observed between the departments in other parameters. CONCLUSION: In cases of intact tubal pregnancy, four-fifths of obstetric and gynecological departments perform laparoscopic salpingectomy, while only one-fifth utilize systemic methotrexate for treatment. On the other hand, methotrexate is used by one-third to two-fifths of departments of all sizes in cases of atypical ectopic pregnancy localization.
Keywords: methotrexát; interstitial pregnancy; Abortifacient Agents, Nonsteroidal; těhotenství; salpingostomy; lidé; Česká republika; cesarean scar pregnancy; abortiva nesteroidní; průzkumy a dotazníky; salpingektomie; cervical pregnancy; Czech Republic; ženské pohlaví; Humans; questionnaire study; Methotrexate; Pregnancy; Surveys and Questionnaires; Pregnancy, Ectopic; ectopic pregnancy; Female; mimoděložní těhotenství; Salpingectomy